Outcome of Colostomy Closure without Prior Conventional Bowel Preparation - Hamza Sohail, Tahir Shahzad Nawaz Babar, Erum Sarwar, Faryal Sadaqat, Muhammad Asjad Saleem, Muhammad Munwar Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine outcome of colostomy closure without prior conventional bowel preparation. A cross-sectional study was conducted at the department of pediatric surgery, Nishtar Hospital, Multan between May 2020 to February 2021. Results: Out of these 102 study cases, 66 (64.7%) were boys and 36 (35.3%) were girls while male to female ratio was 1.83:1. Mean age of our study cases was 6.19 ± 2.64 years (with minimum age was 2 years while maximum age was 12 years). Mean duration of surgery in our study cases was 105.88 ± 18.55 minutes (with minimum duration of the surgery was 65 minutes while maximum duration of the surgery was 145 minutes). Obesity was noted in 15 (14.7%) of our study cases. Anastomotic leakage was noted in 10 (9.8%), wound infection in 15 (14.7%) and prolonged hospital stay in 30 (29.4%) of our study cases. Conclusion: The results of this study indicate that colostomy closure without prior conventional bowel preparation is a safe, reliable and cost effective mode of treatment. It can be applied to children of different age groups without any significant side effects and it provides less pre-operative hospital stay which is beneficial not only for the parents but also for the hospital authorities. So our study results recommend the use of colostomy closure without prior conventional bowel preparation with desired outcomes.